If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(9x+4)=3(4x+9)
We move all terms to the left:
5(9x+4)-(3(4x+9))=0
We multiply parentheses
45x-(3(4x+9))+20=0
We calculate terms in parentheses: -(3(4x+9)), so:We get rid of parentheses
3(4x+9)
We multiply parentheses
12x+27
Back to the equation:
-(12x+27)
45x-12x-27+20=0
We add all the numbers together, and all the variables
33x-7=0
We move all terms containing x to the left, all other terms to the right
33x=7
x=7/33
x=7/33
| 12x-7x+5x=8(2x+1)+x-8 | | {w}{2}w2-18=-7 | | -13=-b-7 | | -f=-12.7 | | d/5=7.2 | | -f=-12.6 | | 3x+8°=2x+2° | | 15x−11=14x+7 | | -26r=208 | | -3d=-4d-5 | | -17+72=-5(x+2) | | 2=–c4 | | -18(x-9)=-324 | | 4x+2x-7=177 | | 2x+30=114 | | j/20=20 | | 12.5=2g=3.5 | | .5(3x-4)=11 | | 7x+27+60-5=180 | | 10-7g=-5-10g | | 15x+–19x−–8=–8 | | -2+16v=-26+4v | | 45x+20=12x+90 | | 2x+40=114 | | 4(3x+8)=-46+54 | | 83=n+-880 | | 3.1+10m=7.38 | | 22+6h=2(2h-3) | | t/4+15=14 | | |x|=7.19 | | 5(2x-3)=2x-16 | | 7+4j=19 |